1992
DOI: 10.1007/bf00165952
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic findings in eyes treated with a ruthenium plaque for uveal melanoma

Abstract: Fifty-six globes that had to be enucleated following ruthenium plaque therapy were examined histopathologically. These eyes account for 10% of all uveal melanomas treated at the University Eye Clinic Essen up until 1985. All but one revealed at least some supposedly viable tumor cells. The most prominent findings within the tumors were tumor cell necrosis, vacuolization and balloon cell degeneration, vascular obstruction and fibrosis of the tumor stroma with accumulation of pigmented macrophages. Tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 18 publications
0
29
0
4
Order By: Relevance
“…Others believe that Table 4. Predictors of enucleation, tumor recurrence, and poor visual acuity in 51 patients with thick choroidal melanoma (7 mm ≤ thickness < 11 mm) after 106 Ru brachytherapy (poor visual acuity was defined as VA less than or equal to 20/200) indirect tumoricidal effects of radiation through obliterating tumor blood supply can justify lower doses to apex even when the tumor is very thick, and the apex of tumor will receive radiation less than the recommended dose [15,16,34]. Compatible with this theory, some authors [22] have recommended a minimal radiation dose of 300-400 Gy to the sclera for development of choroidal atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Others believe that Table 4. Predictors of enucleation, tumor recurrence, and poor visual acuity in 51 patients with thick choroidal melanoma (7 mm ≤ thickness < 11 mm) after 106 Ru brachytherapy (poor visual acuity was defined as VA less than or equal to 20/200) indirect tumoricidal effects of radiation through obliterating tumor blood supply can justify lower doses to apex even when the tumor is very thick, and the apex of tumor will receive radiation less than the recommended dose [15,16,34]. Compatible with this theory, some authors [22] have recommended a minimal radiation dose of 300-400 Gy to the sclera for development of choroidal atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, another 170 such pathological studies have been reported [24][25][26][27][28][29][30][31]. A substantial number of irradiated tumours are treated successfully, but the actual percentage of loss of proliferative capacity of all stem cells will never be known.…”
Section: Tumour Biology In Relation To Ionising Radiationmentioning
confidence: 99%
“…Appearances suggesting continuing tumour cell activity was noted in rutheniuml~ melanomas in 55 of 56 cases [24]. On the other hand, microscopically complete tumour necrosis was found in 10 out of 25 large melanomas, measuring > 7-8 mm in height after iodine125-brachytherapy [25].…”
Section: Tumour Biology In Relation To Ionising Radiationmentioning
confidence: 99%
“…These intratumoral macrophages often carried pigment and are called melanophages. In another study, two of the most prominent findings within tumors following ruthenium plaque therapy were tumor cell necrosis and an accumulation of pigmented macrophages [51]. Local treatment with thermotherapy also stimulated the influx of macrophages [52].…”
Section: Macrophage-influx After Therapymentioning
confidence: 99%